HISTORIOGRAFI DAN DIALOG LINTAS IMAN: ANALISIS HISTORIS KEPERCAYAAN ALUK TODOLO DI MAPIA, KAPALA PITU,LEMBANG BENTENG MAMULLU, TORAJA UTARA - Presdioyono; Corina Tangdiombo; Inriyani; Irna Bumbungan; Zhirene (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research analyzes the historiography and interfaith dialogue related to the Aluk Todolo belief in Mapia, Kapala Pitu, Lembang Benteng Mamullu, North Toraja. The study focuses on the interaction of ancestral cosmology, the social structure of the tongkonan (traditional tongkonan), and the presence of world religions, particularly Christianity and Catholicism, in shaping local religious historical narratives. Using a qualitative approach, case study design, and narrative analysis, this research reconstructs the community's internal narrative through interviews with tominaa (traditional leaders) and traditional leaders, then places this narrative in critical dialogue with established academic narratives. The findings indicate that the Aluk Todolo ritual is not extinct but is reinterpreted through glocalization, reconstruction of death rites, and interfaith family practices that negotiate the boundaries between traditional and official religions. Interfaith relations are based on tongkonan kinship, while the identities of the younger generation are hybrid, combining official religion with ancestral memories and symbols.